A multicultural success story? Australian integration in comparative focus. (June 2020) - Busbridge, Rachel
Australia is often held up as an exemplary multicultural society in cross-national comparisons, particularly in relation to the integration of immigrants. Yet, this 'grand narrative' of Australia's multicultural success risks an over-simplified picture of the dynamics of integration in Australia, obscuring dimensions on which Australia's performance is comparatively poor. Juliet Pietsch's Race, Ethnicity and the Participation Gap makes a valuable contribution to a more nuanced discussion, asking why the political participation of non-European ethnic and immigrant minorities in Australia is so low compared to Canada and the United States. This review article brings Pietsch into critical conversation with two recent books on comparative integration in North America and Western Europe: Richard Alba and Nancy Foner's S trangers No More and Gulay Ugur Goksel's Integration of Immigrants and the Theory of Recognition . Read alongside each other, these texts encourage deeper reflection on where Australia sits on a variety of indicators of immigrant integration as well as how integration is conceptualised in Australia. This article thus contributes to existing literature on the contemporary state of Australian multiculturalism, while also pointing towards directions for future research.